Climate-Adaptive Architecture: Analysis of the Wei Family Compound’s Thermal–Ventilation Environment in Ganzhou, China - Xiaolong Tao; Xin Liang; Wenjia Liu (Buildings)
Sustainable building design is significantly impacted by the local climate response knowledge ingrained in traditional architecture. However, its integration and dissemination with contemporary green technologies are limited by the absence of a comprehensive quantitative analysis of the regulation of its humid and temperature environment. The Ganzhou Wei family compound from China’s wind–heat environmental regulation systems are examined in this study. We statistically evaluate the synergy between spatial morphology, material qualities, and microclimate using field data with Thsware and Ecotect software in a multiscale simulation framework. The findings indicate that the compound’s special design greatly controls the thermal and wind conditions. Cold alleyways and courtyards work together to maximize thermal environment regulation and encourage natural ventilation. According to quantitative studies, courtyards with particular depths (1–4 m) and height-to-width ratios (e.g., 1:1) reduce wind speed loss. A cool alley (5:1 height–width ratio) creates a dynamic wind–speed–temperature–humidity balance by lowering summer daytime temperatures by 2.5 °C. It also serves as a “cold source area” that moderates temperatures in the surrounding area by up to 2.1 °C. This study suggests a quantitative correlation model based on “spatial morphology–material performance–microclimate response,” which offers a technical route for historic building conservation renovation and green renewal, as well as a scientific foundation for traditional buildings to maintain thermal comfort under low energy consumption. Although based on a specific geographical case, the innovative analytical methods and strategies of this study are of great theoretical and practical significance for promoting the modernization and transformation of traditional architecture, low-carbon city construction, and sustainable building design.